High precision and sensitivity detection of gas measurement by laser wavelength modulation spectroscopy implementing an optical fringe noise suppression method. (July 2023) - Cao, Yanan; Cheng, Xin; Xu, Zong; Tian, Xing; Cheng, Gang; Peng, Feiyan; Wang, Jingjing
Highlights: The new optical fringe noise suppression method with an optimal averaging spectral range is proposed for suppressing the optical fringes noise in the multipath system. Compared with traditional filtering methods (for example, averaging filtering, Savitzky-Golay (S-G) filtering, Stochastic Resonance(SR) filtering and Radio Frequency (RF) noise filtering), the new optical fringe noise suppression method can completely eliminate optical fringes noise and then the SNR of the signal is improved about 6.5 times. Regardless of the magnitude of the optical fringes or the signal type (direct absorption signal, wavelength modulation signal, etc .). The new method is applicable. The new method is not only suitable for optical fringe noise, but also for random noise (for example, white noise). A highly precise and sensitive gas sensor for atmospheric trace was developed, the corresponding CH4 minimum detectable concentration can reach 0.78 ppb. A ∼1.5 times improvement in the measurement precision is achieved compared to unprocessed raw signal. Abstract: In this work, a novel method to suppress optical fringe noise in the tunable diode laser absorption spectroscopy is proposed and applied to the CH4 gas sensor perturbed by optical fringes for higher detection precision and sensitivity. For the 2nd harmonic(2 f ) signal of 20 ppm CH4 spoiled by optical fringes and random noise, by the novel method, the signal-to-noise ratio (SNR) of the 2 f signal is improved about 6.5 times from 17 to 182 with an optimal averaging spectral range Δλ. A ∼1.5 times improvement in the measurement precision of CH4 is achieved compared to unprocessed raw signal. The corresponding minimum detectable concentration can be improved from 3 ppb down to 0.78 ppb. The corresponding noise equivalent absorption sensitivity (NNEA) and the noise equivalent concentration (NEC) of the system is 6.13×10 −11 cm −1  W Hz −1/2 and 0.181 ppm, respectively.